PRODUKSI TEPUNG UBI KAYU BERPROTEIN: KAJIAN PEMANFAATAN TEPUNG KACANG BENGUK SEBAGAI SUMBER NITROGEN RAGI TEMPE - Marniza, Marniza; Medikasari, Medikasari; Nurlaili, Nurlaili (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
Cassava roots have low protein content and short storage life. Fermentation of cassava using tempeh innoculum is one way to increase the protein content of cassava. Cassava has low protein content therefore it needs to add nitrogen for ragi tempeh to grow. Velvet bean could be used to enrich nitrogen source for the growth of tempeh mold in cassava fermentation. The objectives of this research was to determine the influence of addition of velvet bean flour iton cassava fermentation using ragi tempeh which will increase protein content of the cassava and meet SNI standard. The experimental design used was a Completely Group Randomized Design, single factor with six concentration level : 0%; 6%; 8%; 10%; 12%; 14% with three replications. Data was evaluated using Bartlett test, Tukey test and BNT 5%. The high protein content 11,51% was obtained from the addition of velvet bean flour at concentration of 12%. The mousture and HCN content in all treatments have meet the SNI 01-2997-1992 standard for cassava flour, but not for minerals and starch contents.